2011
DOI: 10.1016/j.ajpath.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Plague in Guinea Pigs and Its Prevention by Subunit Vaccines

Abstract: Human pneumonic plague is a devastating and transmissible disease for which a Food and Drug Administration-approved vaccine is not available. Suitable animal models may be adopted as a surrogate for human plague to fulfill regulatory requirements for vaccine efficacy testing. To develop an alternative to pneumonic plague in nonhuman primates, we explored guinea pigs as a model system. On intranasal instillation of a fully virulent strain, Yersinia pestis CO92, guinea pigs developed lethal lung infections with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The protective efficacy of recombinant F1 and V subunits against Y. pestis has been reported by a number of laboratories and in a range of laboratory animal models including guinea pigs [48,61], rats [62] and non-human primates [50,63]. Vaccination with these sub-units has been shown to protect animal models against flea-vectored plague [64] as well as against experimental Y. pestis challenges, including pneumonic infections [45,62,63,65], unlike KWCVs.…”
Section: Prospects For Vaccinationmentioning
confidence: 99%
“…The protective efficacy of recombinant F1 and V subunits against Y. pestis has been reported by a number of laboratories and in a range of laboratory animal models including guinea pigs [48,61], rats [62] and non-human primates [50,63]. Vaccination with these sub-units has been shown to protect animal models against flea-vectored plague [64] as well as against experimental Y. pestis challenges, including pneumonic infections [45,62,63,65], unlike KWCVs.…”
Section: Prospects For Vaccinationmentioning
confidence: 99%
“…When used as a vaccine in mice, rats, guinea pigs and non-human primates, rV10 immunization offered significant protection against pneumonic plague challenge [24, 4648]. Analysis of IgG responses to immunization revealed that, in contrast to wild-type LcrV, rV10 vaccine elicited almost exclusively antibodies that recognize conformational epitopes on the plague antigen [47, 48]. …”
Section: Introductionmentioning
confidence: 99%
“…We chose serum specimens in our study because blood is the most accessible and frequently assayed bodily fluid, and the most dangerous clinical presentations of plague are primarily from pneumonic and septicemic cases in which no buboes are present (Williams et al 1972). The detection limit when using silver enhancement was 10 2 -10 4 CFU/ml of Y. pestis, which was close to (or even better than) the sensitivity of mouse bioassay (10 3 CFU/ml, Quenee et al 2011). This enhanced strip assay is sufficiently sensitive to support effective in vitro Y. pestis distribution analysis and for use in field contamination detection, especially in cases of bioterrorist attacks that use plague as a biological weapon.…”
Section: Discussionmentioning
confidence: 98%